Obesity and Skull Base Manifestations: Clinical Implications and Management - Mohamad R. Chaaban; Jessica W. Grayson; Kristen O. Riley; Bradford A. Woodworth (Journal of Clinical Medicine, 2026)
Obesity has become an important modifier of skull base disease. Although obesity is discussed in the context of obstructive sleep apnea, anesthesia risk, and wound healing, its most important skull base manifestation is often mediated through chronically elevated intracranial pressure. Spontaneous cerebrospinal fluid (CSF) leaks and skull base encephaloceles are now widely recognized as acquired defects that commonly arise in overweight or obese patients with idiopathic intracranial hypertension (IIH). This relationship has direct implications for diagnosis, surgical planning, reconstruction, postoperative management, and long-term recurrence prevention. Importantly, patients with active spontaneous CSF leaks may not display the classic signs of IIH because the leak itself may provide partial CSF diversion. Thus, the absence of papilledema or visual symptoms should not falsely reassure the clinician that intracranial pressure is normal. Obstructive sleep apnea may further contribute to intermittent intracranial pressure elevation through hypoxia, hypercapnia, and impaired venous drainage, and it creates unique perioperative challenges after endoscopic skull base reconstruction because positive airway pressure must be balanced against the need to protect the repair. This review summarizes the pathophysiology, clinical presentation, diagnostic evaluation, and management of obesity-associated skull base manifestations, with emphasis on spontaneous CSF leaks, encephaloceles, IIH, obstructive sleep apnea, endoscopic repair, intracranial pressure management, and postoperative airway considerations.